Case report: Long-term follow-up of a large full-thickness skin defect treated with a photosynthetic scaffold for dermal regeneration - Obaíd, Miguel L.; Carvajal, Felipe; Camacho, Juan Pablo; Corrales-Orovio, Rocío; Martorell, Ximena; Varas, Juan; Calderón, Wilfredo; Guzmán, Christian Dani; Brenet, Marianne; Castro, Margarita; Orlandi, Cecilia; San Martín, Sebastián; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
It is broadly described that almost every step of the regeneration process requires proper levels of oxygen supply; however, due to the vascular disruption in wounds, oxygen availability is reduced, being detrimental to the regeneration process. Therefore, the development of novel biomaterials combined with improved clinical procedures to promote wound oxygenation is an active field of research in regenerative medicine. This case report derives from a cohort of patients enrolled in a previously published ongoing phase I clinical trial (NCT03960164), to assess safety of photosynthetic scaffolds for the treatment of full skin defects. Here, we present a 56 year old patient, with a scar contracture in the cubital fossa, which impaired the elbow extension significantly affecting her quality of life. As part of the treatment, the scar contracture was removed, and the full-thickness wound generated was surgically covered with a photosynthetic scaffold for dermal regeneration, which was illuminated to promote local oxygen production. Then, in a second procedure, an autograft was implanted on top of the scaffold and the patient’s progress was followed for up to 17 months. Successful outcome of the whole procedure was measured as improvement in functionality, clinical appearance, and self-perception of the treated area. This case report underscores the long-term safety and applicability of photosynthetic scaffolds for dermal regeneration and their stable compatibility with other surgical procedures such as autograft application. Moreover, this report also shows the ability to further improve the clinical outcome of this procedure by means of dermal vacuum massage therapy and, more importantly, shows an overall long-term improvement in patient´s quality of life, supporting the translation of photosynthetic therapies into human patients.